PERBEDAAN ANTARA AQUATIC EXERCISE DENGAN MCKENZIE EXERCISE DALAM MENURUNKAN DISABILITAS PADA PENDERITA DISCOGENIC LOW BACK PAIN - Budi Susanto; N. Adiputra; Sugijanto - (Sport and Fitness Journal, 2015)
Low Back Pain is one of the most musculoskeletal problem. LBP can cause disability,material loss and biopsychosocial problem. The most effective management for LBP is stilldiscussing in the health practitioner and scientist between Aquatic Exercise or McKenzieExercise. The aim of this study is to prove the different between Aquatic Exercise withMcKenzie Exercise to reduce disability in Discogenic Low Back Pain patients. This studywas the true experimental control trial research, with randomized pre-test and post-testdesign. The study was conducted in Physiotherapy Clinic in Borromeus Hospital Bandungand Melinda Surgery Hospital Bandung. The samples were 19 divided into two groups.Group I with Aquatic Exercise was 9 people and Group II with McKenzie Exercise was 10people. The measuring instrument in this study was Oswestry Disability Index. Results of thehypothesis used paired t-test and independent t-test. The hypothesis test results showed thatboth of groups can reduce disability significantly with mean in Group I = 25,9248 ± 3,98214,p value = 0.001 (p < 0.05) and Group II = 16,912 ± 4,0873, p value = 0.001. And between 2groups there were significant difference with mean = 8,57193 ± 3,66789, p value = 0.032 (p< 0.05). The conclusions where both of Aquatic Exercise and McKenzie Exercise couldreduced disability significantly and Aquatic Exercise was better than McKenzie Exercise toreduce disability in Discogenic Low Back Pain patients. This study can be suggested that thisAquatic Exercise program to reduce disability in Discogenic Low Back Pain. The multicenter study should be held with longer time and much more subjects.Key